Amelioration of oxygen-induced retinopathy in neonatal mice with fetal growth restriction - Watanabe, Ryusuke; Liu, Shuang; Sakaue, Tomohisa; Ikegawa, Yasuhito; Ohta, Masaaki; Higaki, Takashi; Mogi, Masaki; Eguchi, Mariko (Frontiers in Cell and Developmental Biology, 2024)
Introduction: With the aim of optimizing the balance of maintaining a safe oxygen saturation and reducing the risk of retinopathy of prematurity (ROP) in human neonates with fetal growth restriction (FGR), the present study investigated the distinct effects of oxygen supplementation on the retinal neovasculature using a murine premature neonatal oxygen-induced retinopathy (OIR) model with or without FGR. Methods: For comparison with normal birth-weight neonates, maternal low-protein diet-induced FGR neonates were subjected to fluctuating oxygen levels to generate OIR. The retinal neovasculature was histologically evaluated, and comprehensive transcriptome analysis was conducted. Results: Compared to OIR neonates with normal birth weight, significant amelioration of the neovasculature, as indicated by decreases in the number of branch junctions, vascular distribution, maximal vascular radius and microaneurysm-like tufts, was observed in OIR mice with FGR. The results of retinal RNA-sequencing revealed down-regulation of angiogenic factors that trigger pathological retinal neovascularization, such as the MAPK pathway and corresponding upstream signaling pathways in OIR mice with FGR. Conclusion: Our findings demonstrated that FGR neonates have a higher capacity for retinal oxygen stress, and the risk of OIR development is attenuated compared to that in mature neonates with normal birth weight.